1991
DOI: 10.1128/jb.173.18.5663-5667.1991
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular structure and aggregation states of Helicobacter pylori urease

Abstract: Urease purified from Helicobacter pylori by differential ultracentrifugation and fast pressure liquid chromatography was composed of subunits with apparent molecular weights (MrS) of 66,000 and 30,000. Electron microscopy of this purified material demonstrated that it formed disc-shaped macromolecular aggregates that were approximately 13 nm in diameter and 3 nm thick. Images of both negatively stained and shadowed preparations indicated that the discs tended to stack to form pairs and then these pairs further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 29 publications
(23 reference statements)
1
21
0
Order By: Relevance
“…We find that indeed both particles are similar and, although we were able to differentiate between some particles in favorable orientations, it is easy to confuse them. Our present data also indicate that the heterogeneity observed in earlier preparations of urease (1) arose from contaminating chaperonin particles.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…We find that indeed both particles are similar and, although we were able to differentiate between some particles in favorable orientations, it is easy to confuse them. Our present data also indicate that the heterogeneity observed in earlier preparations of urease (1) arose from contaminating chaperonin particles.…”
supporting
confidence: 68%
“…In the second and most commonly observed orientation, which we interpret as particles being viewed from the side, the image was characterized instead by 13-nm-long and approximately 2-to 3-nm-thick lines that usually occurred as stacks of four. These two views establish that the Hp6OK macromolecular assemblies were built up from discs, probably containing seven subunits, that stacked side by side in a manner analogous to that observed for negatively stained preparations of other GroEL chaperonin assemblies (2, 3, 10-12, 18) and those previously reported as stacked aggregates of urease (1). Examination of mixtures containing purified urease and purified Hp6OK from H. pylon demonstrates that the morphologies and dimensions of the two molecules are very similar (Fig.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…This is also the case with CCUG 915. The adhesin was produced in significant quantities by each of the strains of H. pylori that we examined and was readily isolated, albeit often copurifying with the large urease complex which is produced by this organism in prodigious amounts (2) and the fimbrial filaments mentioned above. Although it is present in significant quantity on the H. pylori surface, the protein appears to be poorly immunogenic in rabbits.…”
Section: Methodsmentioning
confidence: 99%
“…The protein was first isolated from cells of H. pyloni NCTC 11637. Vortexing the bacterial suspensions resulted in release of these amorphous aggregates into the supernatant along with other H. pylon surface components including flagellar filaments and the characteristic doughnut-shaped urease multimer (2). Later examination revealed that not all of the 19.6-kDa proteins (the component that makes up the amorphous aggregates) were removed by this treatment.…”
Section: Methodsmentioning
confidence: 99%